Enhancing Students’ Self-Control Through Sociodrama-Based Group Counseling - Barep Hapit Surya Putra; Ageng Triyono (Jurnal Ilmu Pendidikan (JIP) STKIP Kusuma Negara, 2026)
Adolescent self-control is a critical developmental competency associated with academic achievement and positive social behavior. This study examines the effectiveness of group counseling with sociodrama technique in improving the self-control of Grade XI students at SMA Muhammadiyah 3 Yogyakarta. A quasi-experimental design with a nonequivalent control group was employed. The experimental group (n = 33) participated in structured sociodrama-based group counseling sessions, while the control group (n = 38) received no structured intervention. Self-control was measured using a validated Likert-scale instrument based on Averill's three-dimensional model (behavioral, cognitive, and decisional control). Data were analyzed using paired-sample and independent-sample t-tests at  alpha = 0.05. Results demonstrated a statistically significant improvement in the experimental group (t(32) = 24.456, p < 0.001; mean gain = 11.97 points), compared to a negligible gain in the control group (mean gain = 1.39 points). The between-group comparison was also significant (t(69) = 4.050, p < 0.001). These findings confirm that sociodrama-based group counseling is an effective, engaging, and evidence-based strategy for developing adolescent self-regulation in school settings.